The Routledge anthology of U.S. drama, 1898-1949 - Polster, Joshua E. (Routledge, 2017)
"This collection is organized around key thematic perspectives from colonialism to psychoanalysis, viewing the artistic output of this era through the socio-political events and controversies that shaped it. Each play is accompanied by a critical commentary from a leading scholar and a set of archive source materials, including playbills, production shots, reviews, essays, poems, newspaper articles and official documents. These supplements bring to life the rich and diverse theatre cultures that operated in the United States during this period and explore the essential ways that these cultural artifacts engaged with the national debates that surrounded them."--Provided by publisher.